PENGARUH PENGGUNAAN REKAM MEDIS ELEKTRONIK TERHADAP KEPUASAN PETUGAS REKAM MEDIS DI RS X - Wahyudi, Aldi; Wahab, Syaikhul (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2024)
Electronic Medical Records (EMR) are Medical Records (MR) created using an electronic system intended for the administration of MR. User satisfaction in using EMR is considered a measure of success or failure of the implementation or use of an information system. This satisfaction is an assessment related to whether the performance of an information system is categorized as good or bad and whether the information system used meets the intended purpose. This research goals to know what extent does the use of EMR impact on the satisfaction of MR officers. The research strategy used in this study is a survey-based descriptive quantitative method. The population in this study comprises all Medical Record officers at Hospital X, totaling 14 individuals. A total sampling technique was employed, yielding a sample size of 14 persons. Data collection was conducted through a questionnaire. The results of this study, based on a simple linear regression test, show a sig. value of 0.001 < 0.05, indicating that the variable of EMR usage affects the variable of medical record officers’ satisfaction. The conclusion of this study is that the use of EMR has a significant impact on the satisfaction of medical record officers. The satisfaction of MR officers at Hospital X is influenced by the use of electronic MR by 60.6%, while 39.4% is affected by other variables that not examined in this study.